2015
DOI: 10.1371/journal.pone.0136015
|View full text |Cite
|
Sign up to set email alerts
|

CsBAFF, a Teleost B Cell Activating Factor, Promotes Pathogen-Induced Innate Immunity and Vaccine-Induced Adaptive Immunity

Abstract: B cell activating factor (BAFF) is a member of the tumor necrosis factor family that is known to play an important role in B cell activation, proliferation, and differentiation in mammals. However, studies of BAFF in teleosts are very limited and its function, in particular that under in vivo conditions, is essentially unknown. In this study, we conducted in vivo as well as in vitro functional analyses of a BAFF homologue (CsBAFF) from the teleost fish tongue sole (Cynoglossus semilaevis). CsBAFF is composed o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(18 citation statements)
references
References 63 publications
(59 reference statements)
0
18
0
Order By: Relevance
“…; Meng, Sun & Xu ). However, a vaccination study of tongue sole Cynoglossus semilaevis (Günther) suggested that BAFF enhanced the immunoprotection primed by a DNA vaccine and augmented the production of antibodies (Sun & Sun ). However, in the present study, BAFF expression levels in the first infection and reinfection group did not constitute any trends with IgM sec expression in the posterior kidney or of IgM+ B cells in the blood.…”
Section: Discussionmentioning
confidence: 99%
“…; Meng, Sun & Xu ). However, a vaccination study of tongue sole Cynoglossus semilaevis (Günther) suggested that BAFF enhanced the immunoprotection primed by a DNA vaccine and augmented the production of antibodies (Sun & Sun ). However, in the present study, BAFF expression levels in the first infection and reinfection group did not constitute any trends with IgM sec expression in the posterior kidney or of IgM+ B cells in the blood.…”
Section: Discussionmentioning
confidence: 99%
“…The homologue sequences to mammalian BAFF have been reported in many teleost fish species including rainbow trout ( 41 ), zebrafish ( 120 ), mefugu ( Takifugu obscurus ) ( 121 ), Japanese sea perch ( Lateolabrax japonicus ) ( 122 ), grass carp ( Ctenopharyngodon idella ) ( 123 ), yellow grouper ( Epinephelus awoara ) ( 124 ), miiuy croaker ( Miichthys miiuy ) ( 125 ), tongue sole ( Cynoglossus semilaevis ) ( 126 ), Nile tilapia ( Oreochromis niloticus ) ( 127 ), rock bream ( Oplegnathus fasciatus ) ( 128 ), and also in cartilaginous fish such as white-spotted catshark ( Chiloscyllium plagiosum ) ( 129 ), spiny dogfish ( Squalus acanthias ) ( 130 ), and small-spotted catshark ( Scyliorhinus canicula ) ( 131 ) (summarized in Table 3 ). Interestingly, some studies have revealed that many cartilaginous and bony fish species have more than one BAFF gene ( 51 , 54 ), representing two distinct groups.…”
Section: B Cell-activating Factor Of the Tnf Familymentioning
confidence: 99%
“…Recombinant BAFF proteins have been generated in some of these fish species, such as, for example, the cartilaginous fish white-spotted catshark ( 129 ), and the teleost zebrafish ( 120 ), fugu ( 121 ), Japanese sea perch ( 122 ), yellow grouper ( 124 ), tongue sole ( 126 ), rock bream ( 128 ), or tilapia ( 127 ), to carry out functional studies. These studies have proven an increase on the number of leukocytes mediated by BAFF, although the authors did not clarify whether this was due to a promotion of cell survival or an increase on cell proliferation, and they did not demonstrate if the surviving/proliferating fish leukocytes were in fact B cells.…”
Section: B Cell-activating Factor Of the Tnf Familymentioning
confidence: 99%
“…Briefly, a PoPTEN specific siRNA (5′-GCACTTCAACATCCGTCAC-3′) was inserted into the siRNA expression vector pRNAT-CMV3.1 (GenScript, Piscataway, NJ, USA) at BamH I/Alf II restriction sites, resulting in plasmid pPoPTENsi. The inhibitory effect of pPoPTENsi on PoPTEN expression in flounder tissues was verified by qRT-PCR as reported previously [ 102 ]. The negative control plasmid, pPoPTENsiC, which expresses a scramble siRNA (5′-ACCTACTGCGCTTAACACC-3′), was similarly constructed.…”
Section: Methodsmentioning
confidence: 64%
“…The PCR product was ligated into pCN3 [ 101 ] at the EcoR V site, resulting in pPoPTEN. The plasmid pPoPTENsi used for the knockdown of PoPTEN was constructed by using siRNA as reported previously [ 102 ]. Briefly, a PoPTEN specific siRNA (5′-GCACTTCAACATCCGTCAC-3′) was inserted into the siRNA expression vector pRNAT-CMV3.1 (GenScript, Piscataway, NJ, USA) at BamH I/Alf II restriction sites, resulting in plasmid pPoPTENsi.…”
Section: Methodsmentioning
confidence: 99%